2016
DOI: 10.3389/fvets.2016.00107
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Topiramate: Pharmacokinetics in Dogs with Naturally Occurring Epilepsy

Abstract: RationaleBarriers to developing treatments for human status epilepticus include the inadequacy of experimental animal models. In contrast, naturally occurring canine epilepsy is similar to the human condition and can serve as a platform to translate research from rodents to humans. The objectives of this study were to characterize the pharmacokinetics of an intravenous (IV) dose of topiramate (TPM) in dogs with epilepsy and evaluate its effect on intracranial electroencephalographic (iEEG) features.MethodsFive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Over the past 15 years, several peer‐reviewed NLME analyses in veterinary pharmacology have been published. The most recent examples include the study of topiramate in epileptic dogs (Vuu et al., ); nonsteroidal anti‐inflammatory drug (NSAIDs) in dogs and cats with osteoarthritis (Cox, Liao, Payne‐Johnson, Zielinski, & Stegemann, ; Fink et al., ; Pelligand, Soubret, King, Elliott, & Mochel, ; Silber et al., ); tobramycin in horses (Haritova, Bakalov, Hubenov, & Lashev, ); valnemulin and cefquinome in pigs (Zhao et al., , ); tulathromycin in lactating goats (Lin, Cuneo et al., ; Lin, Gehring et al., ); and penicillin G in cattle and swine (Li et al., ).…”
Section: Applications In Veterinary Medicinementioning
confidence: 99%
“…Over the past 15 years, several peer‐reviewed NLME analyses in veterinary pharmacology have been published. The most recent examples include the study of topiramate in epileptic dogs (Vuu et al., ); nonsteroidal anti‐inflammatory drug (NSAIDs) in dogs and cats with osteoarthritis (Cox, Liao, Payne‐Johnson, Zielinski, & Stegemann, ; Fink et al., ; Pelligand, Soubret, King, Elliott, & Mochel, ; Silber et al., ); tobramycin in horses (Haritova, Bakalov, Hubenov, & Lashev, ); valnemulin and cefquinome in pigs (Zhao et al., , ); tulathromycin in lactating goats (Lin, Cuneo et al., ; Lin, Gehring et al., ); and penicillin G in cattle and swine (Li et al., ).…”
Section: Applications In Veterinary Medicinementioning
confidence: 99%
“…The canine pharmacology profile was investigated by Streeter et al 9 . and recently by Vuu et al 10 ,. which revealed appropriate clinical properties that can assist in developing future clinical trials.…”
Section: Discussionmentioning
confidence: 76%
“…It was evaluated as an add-on AED for refractory idiopathic epilepsy in dogs, 2 neuropathic pain in Chiari-like malformation, 6 and feline idiopathic ulcerative dermatitis. 7,8 The canine pharmacology profile was investigated by Streeter et al 9 and recently by Vuu et al 10 , which revealed appropriate clinical properties that can assist in developing future clinical trials. On an open-label clinical trial of topiramate in idiopathic epileptic seizures, 2 five of 10 dogs had more than 50% reduction in seizure frequency during the 2 months evaluation period.…”
Section: Discussionmentioning
confidence: 99%
“…the parameters related about drug elimination greatly. Therefore, the parameters of elimination half-life (~10 h) was longer the references reported (3.7-5 h) [37]. It was reported that the mean plasma elimination half-life was 19-23 h in healthy volunteers without enzyme induction.…”
Section: Plos Onementioning
confidence: 68%
“…It was reported the effective blood concentration of TPM in human with status epilepticus was 2-40 μg/mL [37]. Based on this, the blood drug concentration of PPOP tablets here might be unable to produce sufficient therapeutic effect in vivo.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 84%